PEER EDUCATOR DAN PENDIDIKAN KESEHATAN REPRODUKSI REMAJA - , ALI IMRON; , Dr. Partini, SU, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One of the present important development issues was reproduction health. The reproduction health began at adolescence and adolescents became primary concern. Additionally, labile condition, less understanding of the right reproduction health and the taboo of sex caused reproduction deviations such as premarital sex, abortion and HIV/AIDS. However, there were many refproduction information that were easily accessed by adolescents and parents could not play maximal role in the reproduction health education because they were lack of the knowledge of the reproduction health in addition to the existing social construct that considered sexuality as taboo. Peer educator approach in the adolescent reproduction health education was chosen because peers played an important role in transfering the information of the reproduction health. The effectiveness of the peer education approach in the program PIK-KRR became the entry point in the adolescent reproduction health education. The study used qualitative method and was conduced in âDemarkoâ Senior High School. The informants were selected using purposive sampling except those in selected using snowball sampling. The data was collected using participant observation and in-depth interview for descriptive analysis. The adolescent reproduction health education wass conducted through Pusat Information dan Konseling Kesehatan Reproduksi Remaja (PIK-KRR) program and the peer educator as the primary actor. The PIK-KRR of âDemarkoâ Senior High School is referred to as âSuburâ. Though it was controversial at the beginning, the PIK-KRR âSuburâ obtains the predicate âTegarâ representing the highest level in the management of the PIK-KRR. However, in the first year the management of the PIK-KRR managed to organize all of the programmed activities and won First Champion of PIK-KRR at provincial level. In the next operation, it was proven that the performance of the peer edcuators in the PIK-KRR âSuburâ decreased because the communication went unidirectionally, is of low intensity, gains less support and appreciation of the school and the low motivation of advocating teachers. Some actors in the implementation of the PIK-KRR in âDemarkoâ Senior High School pursued their own interests. The articulation of the actors blured the objective of the reproduction health education that the program did not go effectively.